2015
DOI: 10.1002/ange.201501556
|View full text |Cite
|
Sign up to set email alerts
|

Eine additivarme photoredoxkatalysierte reduktive Kupplung von Aldehyden, Ketonen und Iminen mit sichtbarem Licht

Abstract: Ketylradikale und Aminoradikalanionen sind interessante reaktive Intermediate für C-C-Kupplungen. Dennoch ist die Verwendung dieser reaktiven Intermediate in der Katalyse nur spärlich beschrieben. Grund hierfür sind die thermodynamischu ngünstigen Verhältnisse einer Carbonyloder Imin-Umpolung mittels der Redoxkatalysatoren. Im Rahmen des reduktiven Lçschzyklus in der Photoredoxkatalyse kommen gewçhnlicht ertiäre Amine als Coreduktionsmittel zum Einsatz, die keine weitere nennenswerte Funktion erfüllen. Wir zei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…[1] As depicted in Scheme 1, the substrate scope for lightinduced single-electron transfer (SET) process is confined by ground state and excited state redox potentials of the photocatalyst (PC), that is, E([PC] +/ *) and E([PC] 0/À ). [2,3] Fort he widely used photo-reductant [Ir(ppy) 3 ], its E([PC] +/ *) is À1.73 Vv ersus the saturated calomel electrode (SCE).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1] As depicted in Scheme 1, the substrate scope for lightinduced single-electron transfer (SET) process is confined by ground state and excited state redox potentials of the photocatalyst (PC), that is, E([PC] +/ *) and E([PC] 0/À ). [2,3] Fort he widely used photo-reductant [Ir(ppy) 3 ], its E([PC] +/ *) is À1.73 Vv ersus the saturated calomel electrode (SCE).…”
mentioning
confidence: 99%
“…We propose to develop strong photo-reductants with blue phosphorescent tetradentate platinum(II) complexes [10] for the following reasons.First, the high energy (E em )and tens of microseconds lifetime of the triplet excited states of blue phosphorescent metal complexes are instrumental to achieve strongly reducing excited state species ([PC]*) for efficient bimolecular photochemical reactions.S econd, the strong chelate effect of tetradentate ligand scaffold renders the platinum photo-catalyst robust against demetallation both in the ground and excited states.Third, Pt II complexes with open coordination sites may activate chemical bonds via innersphere atom transfer process.I nt his work, we chose Pt II complexes supported by the bis(phenolate-NHC) ligands bearing electron-donating N-carbazolyl groups (1 and 2, Figure 1). Theanalogue bearing strong electron-withdrawing CF 3 (3)a nd the other complexes,[ Pt(ppy)(acac)],[ Pt(pim)-(acac)] and [Ir(ppy) 3 ]w ere studied for comparison.…”
mentioning
confidence: 99%
“…A detailed analysis of the catalytic cycle, and of all data were crucial in order to understand the failure, and to the reprojection of experiments. The proposed catalytic cycle, that is following the proposals discussed in publication by Rueping [31] and us [25] is reported in Figure S8 in SI.…”
Section: Resultsmentioning
confidence: 95%
“…Coumarins can be accessed by straightforward synthesis [27] that gives the possibility to vary their photophysical and redox properties, [28] allowing to cover a wide range of redox potentials in their ground and excited state. With all these potentialities, we have applied coumarin dyes as powerful photoreductant in pinacol coupling, [25,29,30] replacing the use of iridium complexes for this transformation [31] . In addition, we have shown that a completely different mechanistic picture is operating [25] and that the coumarin dyes, in their excited state, are able to directly reduce carbonyls to the corresponding ketyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Vorkurzem haben wir über eine photoredoxkatalytische Pinakol-Kupplung berichtet, bei der die Bildung der schwer zugänglichen intermediären Ketylradikale durch einen protonengekoppelten Elektronentransferprozess (PCET) realisiert wurde;dabei gelang uns ebenso die reduktive Dimerisierung von Aldiminen. [5] Die gezielte Nutzung persistenter sekundärer a-Aminoradikalanionen (I) ausgehend von Iminen wurde ebenfalls von den Gruppen um MacMillan und Ooi beschrieben. [6] Die Generierung sekundärer a-Aminoradikalanionen durch SET-Umpolung ist ein komplementärer Ansatz zur etablierten SET-Oxidation von Aminen, [7] die über den letztgenannten Reaktionspfad nur schwer zugänglich sind.…”
unclassified